2017
DOI: 10.1002/jcp.25953
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor effects of crocetin and related molecular targets

Abstract: Natural products have gained a wide popularity as chemopreventive and anti-cancer agents owing to their multi-mechanistic mode of action, availability and synergism with several conventional chemotherapeutic agents. Crocetin is a carotenoid compound isolated from the stigma of Crocus sativus L. (saffron). Crocetin has shown promising effects as an anti-tumor agent in animal models and cell culture systems. Crocetin retards the growth of cancer cells via inhibiting nucleic acid synthesis, enhancing anti-oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…A number of previous researches have elucidated that crocetin can inhibit cancer with different mechanisms, such as anti-proliferative and anti-metastatic actions, as well as inducing apoptosis, inhibiting nucleic acid synthesis and enhancing anti-oxidative system [45]. In the present study, the data revealed that crocetin suppressed GC progression via inhibiting angiogenesis, cell proliferation and EMTmediated metastasis of GC cells and these inhibitory effects of crocetin were associated with attenuated activation of Shh/Gli signaling pathway.…”
Section: Discussionsupporting
confidence: 52%
“…A number of previous researches have elucidated that crocetin can inhibit cancer with different mechanisms, such as anti-proliferative and anti-metastatic actions, as well as inducing apoptosis, inhibiting nucleic acid synthesis and enhancing anti-oxidative system [45]. In the present study, the data revealed that crocetin suppressed GC progression via inhibiting angiogenesis, cell proliferation and EMTmediated metastasis of GC cells and these inhibitory effects of crocetin were associated with attenuated activation of Shh/Gli signaling pathway.…”
Section: Discussionsupporting
confidence: 52%
“…However, resistance to this drug and its toxicity are major problems in the treatment of APL (Tomita et al, ). Plant‐derived bioactive compounds have been shown in numerous studies to exert a variety of antitumor actions, making them potential candidates for adjuvant therapy of different types of cancer (Karthick & Tandon, ; Mirzaei et al, ; Momtazi et al, ; Moradzadeh, Sadeghnia, Tabarraei, & Sahebkar, ). In the previous study, we showed that EGCG increased apoptosis and inhibited telomerase activity in breast cancer cells (Moradzadeh, Sadeghnia, Tabarraei, & Sahebkar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant‐derived bioactive compounds have been shown in numerous studies to exert a variety of antitumor actions, making them potential candidates for adjuvant therapy of different types of cancer (Karthick & Tandon, ; Mirzaei et al, ; Momtazi et al, ; Moradzadeh, Sadeghnia, Tabarraei, & Sahebkar, ). In the previous study, we showed that EGCG increased apoptosis and inhibited telomerase activity in breast cancer cells (Moradzadeh, Sadeghnia, Tabarraei, & Sahebkar, ). In this study, we showed that EGCG decreased proliferation, induced apoptosis, and promoted differentiation in the promyelocytic leukemia cells via inhibition of MDR and PML‐RARα/HDAC1.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenes are vitamin A precursors and some xanthophylls such as L and Z are essential to prevent age-related macular degeneration ( Howitt and Pogson, 2006 ). Furthermore, carotenoids may have anti-cancer activity ( Moradzadeh et al, 2017 ) and some are used as food colorants, and added to cosmetics or pharmaceuticals. One of the few studies on the seeds of wild plant species revealed that grain legumes have lower contents of carotenoids (including those of nutritional value for human and livestock feeding, such as L and Z) than their wild counterparts, indicating a decrease in the concentration of carotenoids in seeds in the course of domestication ( Fernández-Marín et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%